Implementasi Hak Asasi Manusia Dalam Pendidikan Sekolah Dasar (International Forum of Researchers and Lecturers, 2024)
The author believes that the implementation of human rights education in basic education is an important part of basic education. The aim of this research is to explore how human rights education is implemented in basic education. The method used is descriptive qualitative and uses literature studies. The research results show that implementing human rights education in elementary schools is one way to educate children about human rights from an early age. It was also found that the implementation of human rights education in elementary schools is an effort to provide information to children about human rights from an early age.